Link and Match Based Partnership Management in the Fashion Expertise Program at SMK Negeri 6 Semarang - Haq, Arina; Slamet, Achmad; Suminar, Tri (Educational Management, 2019)
In vocational education, cooperation with the business world and industrial world (DU/DI) is very important, and its implementation must be adapted to the needs of the current era. Therefore, Vocational High Schools (SMK) must be able to combine the curriculum and equate perceptions with DU/DI in order to produce quality graduates and have skills that are in line with market needs. This study aimed to describe the relationship of cooperation in the form of partnerships based on link and match in SMK Negeri 6 Semarang, especially in developing competencies in the field of fashion. To be able to achieve the research objectives, a qualitative approach with the case study method was used. The results showed that SMK 6 Semarang had implemented link and match based partnership management in various forms, including: 1). The planning stage begins with synchronizing the curriculum between the school and DU/DI, 2). At the implementation stage, a link and match based partnership program has been implemented in the form of learning and training through holding industrial classes with by-order products that have a sale value, and 3). At the supervision stage, it has collaborated with the Professional Certification Institute (LSP), so as to increase the resources of productive teachers and students in the fashion sector.